Registered report protocol: domestic violence and mental disorders: gender differences and cumulative effects in a Norwegian population - Reneflot, Anne; Straiton, Melanie; Stene-Larsen, Kim; Knudsen, Ann Kristin; Kirkøen, Benedicte; Myklestad, Ingri (Frontiers in Psychiatry, 2025)
IntroductionDomestic violence (DV) is a significant public health problem linked to poor mental health outcomes. Prior research has relied on self-reported symptoms, overlooked mental disorders prevalent in men, inadequately controlled for confounders, and failed to differentiate between forms and severity of DV.MethodsThis registered report protocol outlines the rationale, design, and planned analyses for investigating the relationship between DV and mental disorders in both Norwegian men and women. We will use data from a population-representative psychiatric diagnostic interview survey linked to national health registries. Key confounders, including sociodemographic and health-related variables, will be adjusted for.ResultsWe will examine the association between DV and mental disorders in both men and women, assess cumulative effects of multiple forms of violence, and examine the temporal ordering of DV and mental disorders. Outcomes include anxiety, depression, PTSD, substance use disorder, and suicidality.DiscussionThis study offers population-based insights into the relationship between domestic violence and mental health across genders. The findings may help guide targeted interventions and inform public health policy, particularly in high-income settings.